Injection of Freshly Collected Adipose Tissue for the Treatment Complex Cryptoglandular Anal Fistula: Case Report - Londoño Estrada, Daniel Mauricio; Fernandes, Cristiane Koizimi Martos; Oliveira, Marina Barbarela Grisolia de; Souza, Gustavo Moreira Costa de; Rocha França-Neto, Paulo; Lopes de Queiroz, Fábio; Lacerda-Filho, Antônio (Journal of Coloproctology, 2023)
Introduction Perianal fistula is a common colorectal disease which is caused mainly by cryptoglandular disease. Although most cases are treated successfully by surgery, management of complex perianal fistulas (CPAF) remains a challenge with limited results in recurrence and sometimes associated with fecal incontinence. The CPAF treatment with autologous adipose-derived mesenchymal stem cells (ASCs) had become a research hotspot. The technique started to be used in the treatment of Crohn's disease (CD) fistulas, where the studies showed safe and goods result from the procedure. Cultured ASCs have been used but this approach requires the preceding collection of adipose tissue, time for isolation of ASCs and subsequent in vitro expansion, need for laboratory facilities, and expertise in cell culturing. These factors have been getting over by using the commercially available alternative, allogenic ASCs. Treatment with allogeneic ASCs has shown good results in patients with CD fistulas, however with the disadvantage of being expensive. Objective To show that the injection with freshly collected adipose tissue is an alternative to treatment with autologous or allogenic ASCs with several advantages. Methods: In this case report, we show our first experience in the treatment of CPAF with the application of collected adipose tissue in a tertiary referral hospital from Belo Horizonte, Brazil. Results The patient had a good postoperative recuperation with a complete fistula healing after 8 months without adverse effects. Conclusion Injection with freshly collected adipose tissue is a promising and apparently safe sphincter-sparing technique in the treatment of CPAF.
Keywords: cryptoglandular; Fistula-in-ano; perianal fistula; freshly collected adipose tissue; adipose-derived stem cell; stem cell therapy